Book Review: Ricostruire e Narrare. L’esperienza dei Musei archeologici all’aperto (Reconstructing and storytelling. The experience of archaeological open-air Museums) by M. Valenti - Marco Romeo-Pitone (EXARC, 2020)
This book is particularly welcomed within the scarce Italian literature on the topic of archaeological open-air museums. The lack of debate and accurate information on this type of museums in Italy, drove the author to put together this volume, seven years after the publication of Dr Paardekooper’s magistral “The Value of an Archaeological Open-Air Museum in its use” in 2012, often referred in this book.